Single-cell atlas of domestic pig cerebral cortex and hypothalamus - Zhu, Jiacheng; Chen, Fang; Luo, Lihua; Wu, Weiying; Dai, Jinxia; Zhong, Jixing; Lin, Xiumei; Chai, Chaochao; Ding, Peiwen; Liang, Langchao; Wang, Shiyou; Ding, Xiangning; et al. (Science bulletin, 2021)
[Display omitted] The brain of the domestic pig (Sus scrofa domesticus) has drawn considerable attention due to its high similarities to that of humans. However, the cellular compositions of the pig brain (PB) remain elusive. Here we investigated the single-nucleus transcriptomic profiles of five regions of the PB (frontal lobe, parietal lobe, temporal lobe, occipital lobe, and hypothalamus) and identified 21 cell subpopulations. The cross-species comparison of mouse and pig hypothalamus revealed the shared and specific gene expression patterns at the single-cell resolution. Furthermore, we identified cell types and molecular pathways closely associated with neurological disorders, bridging the gap between gene mutations and pathogenesis. We reported, to our knowledge, the first single-cell atlas of domestic pig cerebral cortex and hypothalamus combined with a comprehensive analysis across species, providing extensive resources for future research regarding neural science, evolutionary developmental biology, and regenerative medicine.